ANALYSIS OF COFFEE FARMERS’ DECISION TO TAKE CREDIT IN PATI REGENCY - Stevana Astra Jaya; Harianto Harianto; M. Parulian Hutagaol (Indonesian Journal of Business and Entrepreneurship (IJBE), 2016)
Coffee Commodities in Pati were undeveloped compared to some other areas in Central Java as a coffee production center. Coffee farmers have some problems in the production of coffee: scarcity of subsidized fertilizers, difficulty to take credit, lack of  dried coffee beans, and damaged roads that lead to expensive production costs. Coffee farmers play a role in the  production activities as decision makers that will directly affect income. The aim of this research was to identify factors that influence the decision of coffee farmers to take credit. The study was conducted in coffee plantations of Klakahkasihan Village, Gembong, Pati. Cross-section data from Sido Makmur farmer group in Klakahkasihan village were collected directly from 52 respondents. They were 32 farmers who took and 20 farmers who did not take credit.  The method used to analyze was probit method analysis. The results showed that the land area and the age of coffee plant variables had a negative coefficients, which means the smaller the land area and the younger the coffee plants, the higher the chances to take the credit. While the number of family members had a positive coefficient, which means that the greater the number of family members, the more chances farmers will take credit. Based on the above results it can be concluded that the farmer's decision to take credit is not for production process, but for other purposes.Keywords:farmer decisions, access credit, coffee plantation,Sido Makmur farmer groups, Pati